Faktor Faktor Yang Mempengaruhi Lama Mencari Kerja Pada Tenaga Kerja Sektor Informal Di Kabupaten Manokwari - Ida A. Baransano; Yuyun P. Rahayu; Lillyani M. Orisu (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
The level of education, age and income, partially and simultaneously affect the length of time on seeking work in Manokwari Regency. BPS data shows the ratio of job seekers is quite large and the number of vacancies is very limited (42 job seekers per 1 job). Competition between job seekers is getting stronger and depends on the background of applicant. In addition, the lack of job seeker background contributes to the longer a person gets a job. This research is a type of quantitative descriptive research and data sources include primary and secondary data. The sampling method is convenience sampling, the number of samples taken is 99 respondents, the data analysis technique in this research is using multiple linear regression. Based on the results of the analysis, it can be seen that the level of education has a negative and significant effect on the length of work seeking. While age has a positive effect and income level has a negative effect on the speed of obtaining one's work, but both do not significantly influence the 95% level of confidence. While the ability of the old variable to find work is explained by the variables of education level, age and income of 99.37%..